Strategies for Biotech Companies to Scale Up Commercially through Effective Project and Risk Management - Varun Choudhary (BULLET : Jurnal Multidisiplin Ilmu, 2022)
Growing biotechnology operations provide potential and problems for businesses across a range of industries, including industry, healthcare, and agriculture. With a focus on efficient project and risk management, this thorough review examines approaches, factors, and implications for commercial scale-up in biotech enterprises. In order to effectively navigate the intricacies of biotech scale-up, align objectives, proactively identify and mitigate risks, optimize resource allocation, and stimulate stakeholder participation and communication, it is imperative that project and risk management methodologies be integrated. Case studies provide best practices and lessons learned from successful commercial scale-up initiatives in the manufacturing of cell therapies, agricultural biotechnology, and biopharmaceuticals. Advances in precision medicine, synthetic biology, digitalization, omics technologies, sophisticated therapeutics, bioprocessing breakthroughs, and international partnerships are some of the future trends and prospects in biotech scale-up. With an emphasis on resource efficiency, renewable energy, waste reduction, green chemistry, biodiversity protection, and life cycle assessment, sustainability and environmental issues are critical to the biotech industry's scale-up. The ethical and social ramifications of biotech scale-up include questions of genetic engineering and manipulation, data ownership and intellectual property, privacy and informed permission, access and equity, dual-use research and biosecurity, environmental sustainability, and social responsibility. Biotech businesses can optimize the advantages of scale-up initiatives while avoiding risks and guaranteeing good societal effect by taking these factors into account and adopting responsible stewardship practices.